2019
DOI: 10.5194/angeo-37-689-2019
|View full text |Cite
|
Sign up to set email alerts
|

Jets in the magnetosheath: IMF control of where they occur

Abstract: Abstract. Magnetosheath jets are localized regions of plasma that move faster towards the Earth than the surrounding magnetosheath plasma. Due to their high velocities, they can cause indentations when colliding into the magnetopause and trigger processes such as magnetic reconnection and magnetopause surface waves. We statistically study the occurrence of these jets in the subsolar magnetosheath using measurements from the five Time History of Events and Macroscale Interactions during Substorms (THEMIS) space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 23 publications
(44 reference statements)
7
63
0
Order By: Relevance
“…The results of our study show that quasi-parallel jets are considerably more frequent than quasi-perpendicular jets. Specifically, similar to recent results (Vuorinen et al, 2019), they were found to occur ∼ 5−10 times more frequently than quasi-perpendicular jets. On average they have a dynamic pressure around 3.5 nPa, with the majority of them exhibiting both a density and a velocity increase.…”
Section: Quasi-parallel and Quasi-perpendicular Jetssupporting
confidence: 89%
See 1 more Smart Citation
“…The results of our study show that quasi-parallel jets are considerably more frequent than quasi-perpendicular jets. Specifically, similar to recent results (Vuorinen et al, 2019), they were found to occur ∼ 5−10 times more frequently than quasi-perpendicular jets. On average they have a dynamic pressure around 3.5 nPa, with the majority of them exhibiting both a density and a velocity increase.…”
Section: Quasi-parallel and Quasi-perpendicular Jetssupporting
confidence: 89%
“…Furthermore, jets can generate a vortical motion in the background magnetosheath plasma, causing a deceleration to the ambient plasma around the jet . It has been recently shown that jets occur roughly 9 times more often downstream of the quasi-parallel bow shock compared to the quasi-perpendicular one (Vuorinen et al, 2019). This is in agreement with the observations showing low solar wind cone angles favoring the creation of subsolar magnetosheath jets, while other solar wind parameter variations have no significant effect (Plaschke et al, 2013).…”
Section: Introductionsupporting
confidence: 88%
“…Furthermore, jets can generate a vortical motion in the background magnetosheath plasma, causing a deceleration to the ambient plasma around the jet (Plaschke & Hietala, 2018). It has been recently shown that jets occur roughly 9 times more often downstream of the quasi‐parallel bow shock compared to the quasi‐perpendicular one (Vuorinen et al, 2019). This is in agreement with the observations showing low solar wind cone angles favoring the formation of subsolar magnetosheath jets, while other solar wind parameter variations have no significant effect (Plaschke et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such magnetosheath jets are characterized by very large dynamic pressure that are comparable to that of the solar wind. Magnetosheath jets are more likely to occur downstream of the quasi-parallel rather than the quasi-perpendicular bow shock (e.g., Plaschke et al, 2013;Vuorinen et al, 2019). One possible reason is that the surface of the quasi-parallel bow shock is rippled (e.g., Gingell et al, 2017;Hao et al, 2017;Karimabadi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%